Vocation: Theory and Practice - Khrypko, Svitlana; Yang, Qi; Stoliarchuk, Olesia; Prorok, Nataliia; Spudka, Iryna; Kalishchuk, Svitlana; Lobanchuk, Olena; Mishchenko-Driuchylo, Viktoriia (Տիգրան Մեծ)
The core paradigm of the role of the phenomenon of vocation in being of a human as a spiritual mystery and a rational choice at the same time is emphasised. We consider the problem of the mystery of vocation in the spiritual-axiological (Christological) context of consideration and secular (so-called profane) understanding with a logical approach to modern-rational, research, and empirical paradigms of under-standing and representation.The work analyses the results of the study of the guidance and actions of Ukrainian psychology students regarding the realisation of one‟s vocation in the field of spiritual searches, in real life and virtual life space. The phenomenon of vocation is considered as a significant personal construct, which becomes a factor in its successful life self-realisation and achievement of psychological well-being. It is stated that a conscious vocation is a key to the successful professional self-determination of a young person and a factor in the effectiveness of their further professionalisation.
Keywords: Social philosophy